Bacterial taxa predictive of hyperpigmented skins. Issue 3 (7th April 2022) - Zanchetta, Catherine; Vilanova, David; Jarrin, Cyrille; Scandolera, Amandine; Chapuis, Emilie; Auriol, Daniel; Robe, Patrick; Dupont, Joran; Lapierre, Laura; Reynaud, Romain
Abstract: Background and Aims: Dark spots, brown spots, or hyperpigmented spots (HPS) are oval or irregular brown areas of skin. Their emergence is associated with dysregulation of the immune system, and may also be caused by a deficiency in stromal cell‐derived factor‐1, leading to perturbed melanogenesis and accumulation of melanosomes within neighboring keratinocytes. The skin microbiota (living microorganisms present on the surface of the skin) is known to play essential roles in maintaining skin homeostasis and in regulating the immune system. Here, we investigated whether the microbiota could play a role in the emergence of HPS. Methods: The clinical study involved 38 European women, selected from among 74 volunteers. Participants were divided into two groups depending on the spot areas measured on their faces. The study was designed to avoid conflicting factors: both groups presented similar skin pH, hydration, transepidermal water loss, and sebum levels. The two cohorts were also age‐matched, with a mean of 29‐years‐old for both. Results: Alpha‐diversity of the microbiota was similar for the two groups. On skins with more HPS, seven bacterial genera were identified in significantly higher proportions and included opportunistic pathogens and inflammatory bacteria. Six bacterial genera, including bacteria showing antioxidant and anti‐UV properties, were identified in significantly higher proportions on less spotted skins. Cross‐domain association networks revealed distinct co‐occurrences of genera between the two groups, suggesting nonidentical community structures and exchanges, depending on the HPS status. Conclusion: Our results reveal specific microbiota composition and networks on skins based on HPS status. Changes could alter communication with the immune system, leading to the emergence of dark spots. As an essential part of the overall skin ecosystem, and through its interaction with the skin matrix, the skin microbiota and its maintenance could be considered a new target for skincare applications.